2021
DOI: 10.1093/brain/awab322
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state EEG reveals four subphenotypes of amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a devastating disease characterised primarily by motor system degeneration, with clinical evidence of cognitive and behavioural change in up to 50% of cases. ALS is both clinically and biologically heterogeneous. Subgrouping is currently undertaken using clinical parameters, such as site of symptom onset (bulbar or spinal), burden of disease (based on the modified El Escorial Research Criteria) and genomics in those with familial disease. However, with the exception of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 70 publications
3
27
0
1
Order By: Relevance
“…Another trend of “big data” interrogation in ALS is the implementation of various clustering approaches to unravel inherent, naturally occurring sub-groups or patient cohorts with distinctive characteristics. A number of recent imaging studies have confirmed the existence of radiological sub-phenotypes using cluster analyses of connectomics [ 108 ], functional [ 109 ], or structural [ 110 ] raw datasets. The inclusion of MRS data into similar clustering pipelines may further help to untangle the heterogeneity of ALS and identify subcohorts with distinctive radiological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Another trend of “big data” interrogation in ALS is the implementation of various clustering approaches to unravel inherent, naturally occurring sub-groups or patient cohorts with distinctive characteristics. A number of recent imaging studies have confirmed the existence of radiological sub-phenotypes using cluster analyses of connectomics [ 108 ], functional [ 109 ], or structural [ 110 ] raw datasets. The inclusion of MRS data into similar clustering pipelines may further help to untangle the heterogeneity of ALS and identify subcohorts with distinctive radiological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were specific to the delta and the theta frequency bands. However, alterations in regional power or static functional connectivity have been described in all frequency bands 36,37 . Ours is the first M/EEG study directly addressing the dynamic, aperiodic, scalefree activity in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…According to Fraschini et al ( Fraschini et al, 2018 ) ALS patients showed reduced brain functional connectivity compared to healthy subjects, which was linked to different synchrony patterns in the alpha band. Nevertheless, alterations in functional connectivity have been reported in all frequency bands ( Dukic et al, 2022 , Nasseroleslami et al, 2019 , Proudfoot et al, 2017 ). Our is the first study which explores the individual connectome features in ALS using the CCF approach.…”
Section: Discussionmentioning
confidence: 99%